Using dissolved oxygen variance to investigate the influence of nonextreme wind events on hypoxia in Mobile Bay, a shallow stratified estuary - Liu, Zhilong; Lehrter, John; Dzwonkowski, Brian; Lowe, Lisa L.; Coogan, Jeff (Frontiers in Marine Science, 2022)
Wind forcing plays an important role in determining spatial patterns of estuarine bottom water hypoxia, defined as dissolved oxygen (DO) concentration< 2 mg L-1, by driving coastal circulation patterns and by intensifying mixing of the water column. However, the importance of these wind-driven mixing processes varies with space and time and are dynamically intermingled with biological processes like photosynthesis and respiration making it difficult to tease apart wind impacts on DO dynamics in estuarine systems. Using a high-resolution, three-dimensional numerical model, we studied the effect of a non-extreme southeast wind event on the DO dynamics of Mobile Bay during a hypoxic event in April-May of 2019. A new approach, called ‘vertical dissolved oxygen variance’ (VDOV) was developed to quantitatively separate all the physical and biogeochemical factors in the water column that control the development and dissipation of hypoxia events. The system-wide volume integrated values of VDOV tracked the changes in hypoxic area in the bay and the VDOV tendency term was dominated by contributions from sediment oxygen demand (DO loss via respiration) and vertical dissipation (DO gain via mixing). There was a notable inverse relationship between hypoxia area and wind speed. Further analysis of the local VDOV during a non-extreme southeast wind event showed the wind-induced vertical dissipation was the main factor in eliminating hypoxia from the bay. This enhanced dissipation accounted for both turbulent mixing from wind stress and negative straining of the vertical density gradient from wind induced circulation. The response of DO to the wind forcing prompted the development of two non-dimensional numbers, an advection-diffusion time-scale ratio and a demand-diffusion flux ratio, to better generalize the expected DO dynamics. Overall, this work showed that wind effects are critical for understanding hypoxia variability in a shallow stratified estuary.